2017
DOI: 10.1016/j.cropro.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anastrepha grandis (Diptera: Tephritidae) under constant temperatures and field validation of a laboratory model for temperature requirements

Abstract: Anastrepha grandis (Macquart) is one of the main pests of cucurbits in the countries of Central and South America. Besides direct damage caused to fruits, A. grandis occurrence in producing regions can lead to export embargos. Despite its economic importance, little is known of the effects of temperature on its biology. This study investigated the development of A. grandis under different temperatures to estimate thermal requirements and then validated the model developed in the field. Development time was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 10 publications
0
21
0
11
Order By: Relevance
“…This fact was evidenced by Stone (1939), who reported high mortality rates in A. striata larvae exposed momentarily to temperatures of 40°C. Similarly, Bolzan et al (2017) reported no embryonic development in regimes above 35°C.…”
Section: Discussionmentioning
confidence: 98%
“…This fact was evidenced by Stone (1939), who reported high mortality rates in A. striata larvae exposed momentarily to temperatures of 40°C. Similarly, Bolzan et al (2017) reported no embryonic development in regimes above 35°C.…”
Section: Discussionmentioning
confidence: 98%
“…In stage‐structured models, the duration of a stage may vary among individuals. For example, eggs laid at the same time do not hatch simultaneously (Bolzan, Nava, Smaniotto, Valgas, & Garcia, ; Moriyama & Numata, ). The same principle applies to any other life stages.…”
Section: Modelsmentioning
confidence: 99%
“…Também, é muito estudado as exigências térmicas de pragas permitindo prever a ocorrência em determinados ambientes (Haddad et al, 1999). Além disso, os estudos de zoneamento climático representados em forma espacial, baseado nos estudos térmicos e número estimado de gerações, são muito utilizados (Milanez et al, 2005;Nava et al, 2005;Nondillo et al, 2008;Freitas Bueno et al, 2009;Neves et al, 2010;Bolzan et al, 2017).…”
Section: Potencial De Alimentação Dos Crisopídeosunclassified
“…O Brasil tem uma diversificada produção agrícola, caracterizada pelas extensas terras férteis e condições climáticas variadas. No entanto, a produção agrícola pode ser afetada negativamente por diversas pragas, causando grandes perdas econômicas ao agricultor em curto período de tempo Graça et al, 2016;Bolzan et al, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation